(untitled) (Research, Society and Development, 2020)
Objective: The objective of this study was to relate the sinus ostium diameter with four known changes in the maxillary sinuses by means of cone beam Computed Tomography (CBCT), considering side and gender. Methodology: 415 CBCT scans were evaluated and a total of 328 CBCT scans from patients over 21 years of age were selected for the study. By means of corrected coronal reconstructions in positioning, an anteroposterior scan of the maxillary sinus region was performed to identify, locate, and measure the diameter of the sinus ostium on the right and left sides. Changes in the maxillary sinuses were considered: thickening of the sinus membrane, antral pseudocyst, partial veiling of the maxillary sinus and total veiling of the maxillary sinuses. Results: There was an influence of sex in the presence of sinus alterations, because in the sample, the odds (odds ratio) of men to have any sinus alteration was 2.44 times (p = 0.0002) greater than in women. In general, regardless of gender, there were no statistically significant differences between the diameters of the left (3.27 ± 1.2 mm) and right (3.12 ± 1.12 mm) ostia. There was also no relationship between age and diameter of ostia, and between age and types of changes sinuses. Conclusion: According to the results obtained, it can be concluded that there is no relationship between the diameter of the sinus ostium of the maxillary sinus and the most frequent sinus changes.